Biguanides suppress hepatic glucagon signalling by decreasing production of cyclic AMP - Miller, Russell A.; Chu, Qingwei; Xie, Jianxin; Foretz, Marc; Viollet, Benoit; Birnbaum, Morris J. (Nature (London), 2013)
Biguanides such as metformin, which is the most widely prescribed drug for type-2 diabetes, are shown to antagonize the actions of glucagon by decreasing the levels of cyclic AMP. Antidiabetics as glucagon antagonists Hyperglycaemia is a common consequence of insulin resistance, the inability of insulin to suppress glucose output by the liver. Biguanides such as phenformin and metformin are often used to lower excessive glucose levels, for example in patients with type-2 diabetes mellitus. Until recently metformin was thought to reduce glucose production by activating AMP-activated protein kinase. Here it is shown, however, that it antagonizes the actions of glucagon. Biguanides increase the levels of intracellular AMP and related nucleotides, thereby inhibiting the ability of glucagon to activate adenylyl cyclase. This results in reduced levels of cyclic AMP and protein kinase A activity, which blocks phosphorylation of substrates that are important for maintaining glucose output from hepatocytes. This work suggests that glucagon antagonists may have antidiabetic potential. Glucose production by the liver is essential for providing a substrate for the brain during fasting. The inability of insulin to suppress hepatic glucose output is a major aetiological factor in the hyperglycaemia of type-2 diabetes mellitus and other diseases of insulin resistance 1 , 2 . For fifty years, one of the few classes of therapeutics effective in reducing glucose production has been the biguanides, which include phenformin and metformin, the latter the most frequently prescribed drug for type-2 diabetes 3 . Nonetheless, the mechanism of action of biguanides remains imperfectly understood. The suggestion a decade ago that metformin reduces glucose synthesis through activation of the enzyme AMP-activated protein kinase (AMPK) has recently been challenged by genetic loss-of-function experiments 4 . Here we provide a novel mechanism by which metformin antagonizes the action of glucagon, thus reducing fasting glucose levels. In mouse hepatocytes, metformin leads to the accumulation of AMP and related nucleotides, which inhibit adenylate cyclase, reduce levels of cyclic AMP and protein kinase A (PKA) activity, abrogate phosphorylation of critical protein targets of PKA, and block glucagon-dependent glucose output from hepatocytes. These data support a mechanism of action for metformin involving antagonism of glucagon, and suggest an approach for the development of antidiabetic drugs.